The Role and Current Status of IFRS in the Completion of National Accounting Rules – Evidence from Finland. (4th May 2017) - Jarva, Henry; Silvola, Hanna
ABSTRACT: We investigate how Finland has applied Directive 2013/34/EU of the European Parliament and of the Council to the annual financial statements, consolidated financial statements and related reports of certain types of undertakings. In addition to the implementation process and general implications of the Finnish Accounting Act, we emphasize its implications and interplay with IFRS. We conclude that the national implementation of Directive 2013/34/EU successfully diminished the administrative burden experienced by small companies.